2017
DOI: 10.3847/1538-4365/aa7517
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Sources Detected in the NuSTAR Serendipitous Survey

Abstract: The Nuclear Spectroscopic Telescope Array (NuSTAR) provides an improvement in sensitivity at energies above 10 keV by two orders of magnitude over non-focusing satellites, making it possible to probe deeper into the Galaxy and universe. Lansbury and collaborators recently completed a catalog of 497 sources serendipitously detected in the 3-24 keV band using 13 deg 2 of NuSTAR coverage. Here, we report on an optical and X-ray study of 16 Galactic sources in the catalog. We identify 8of them as stars (but some … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Then, we find a bright object, CXO J092418.2−314217, in a Swift/XRT soft X-ray image. According to a study by Tomsick et al (2017), it can be classified as the LMXB or the CV, and here we representatively adopt the LMXB. (C) One of the brightest galaxies is selected for the most plausible counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we find a bright object, CXO J092418.2−314217, in a Swift/XRT soft X-ray image. According to a study by Tomsick et al (2017), it can be classified as the LMXB or the CV, and here we representatively adopt the LMXB. (C) One of the brightest galaxies is selected for the most plausible counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Blue circles represent observations from our 2015 decay, with the blue solid lines connecting the data points to illustrate the evolution with time (following the direction of the blue arrow). Red triangles show spectral fits from pre-outburst observations compiled from Reynolds et al (2014) and Rana et al (2016), the red diamond represents a Chandra observation from 2015 November (Tomsick et al 2015), and black squares represent the average photon indices of 10 quiescent BHXBs binned by Eddington ratio, from Plotkin et al (2013). The X-ray spectral softening occurs over a narrow range in Eddington ratio (from than the value for the mechanism that produces the source of seed photons, on account of SSC depending on the product of the photon field density and the particle density (e.g., Falcke & Biermann 1995).…”
Section: Comments On Jet Synchrotron X-ray Emissionmentioning
confidence: 99%
“…et al (2014) and Tomsick et al (2015) in upcoming figures, we convert their reported 0.3-10 keV fluxes to 0.5-10 keV.…”
Section: Quiescent X-ray Spectramentioning
confidence: 99%
See 2 more Smart Citations